ASSESSMENT OF FOREIGN BODIES IN SHEEP RUMEN IN KATSINA METROPOLIS ABATTOIR - Yusuf, A.; Aruwayo, Adebayo; Maigandi, S. A. (FUDMA JOURNAL OF SCIENCES, 2023)
This study was conducted to assess foreign bodies and its impact on the rumen of sheep slaughtered at the Abbattoir in Katsina Metropolis. Sixty six (66) sheep comprising of thirty-three (33) each of ram and ewe were randomly selected for the study. Live-weights of the animals, weight of rumen contents, weight of empty rumen and prevalence of non-biodegradable materials in the rumen were determined based on sex and age. Rumen obstruction determination was also carried out for sheep aged 6, 12 and 18 months of male and female on weekly basis for eleven weeks. The experiment was conducted in a Completely Randomized Design (CRD). The data collected was analysed with Statistical Package for Social Sciences (SPSS). This study showed that 60.60% and 93.93% of the male and female respectively were positive of foreign bodies in their rumen. 87.88% of the sheep sampled had varieties of non-degradable materials in their rumen and pplastics constituted the highest percentage (77.27%). The result revealed that the problem was more common among the age range of 16 and 18 months of age and that sex also has effect on the rate of rumen obstruction with higher occurence in females. The phenomenon of rumen obstruction was discovered to be due to the shortage of feeds and feeding stuff and the resultant scavenging to meet up with nutrient requirement. The findings of this study could help environmental activists, veterinarians, policy makers and livestock owners to recognise the impact of non-bio degradable materials on sheep health and